Impaired Microvascular Response to Muscle Stretching in Chronic Smokers With Type 2 Diabetes - Low, Boon-Hua; Lin, Yue-Der; Huang, Bo-Wen; Chia, Taipau; Bau, Jian-Guo; Huang, Hao-Yu (Frontiers in Bioengineering and Biotechnology, 2020)
Objective: Cigarette smoking promotes endothelial dysfunction and is a prominent catalyst for vascular disease. This study employed laser Doppler flowmetry (LDF) and spectral analysis to investigate the skin microvascular response to relatively mild stimulus of stretching in diabetic smokers. Methods: The study population consisted of thirty type 2 diabetic male patients (15 smokers vs. 15 non-smokers) and 15 normal non-smoking subjects. The cutaneous blood flow of the calf at both lower limbs was measured by LDF at a supine position throughout and after muscle stretching by passive dorsiflexion of the ankle. Results: Following the stretch, post-stretch reactive hyperemia (PSRH) responses were found in all subjects. However, the diabetic non-smokers had relatively higher reactive blood flow than that of the diabetic smokers. The PSRH sustained for a longer time in both diabetic non-smokers and non-diabetic non-smokers in the time domain analysis. By spectral analysis, an observed discrepancy between that of diabetic smokers and diabetic non-smokers was statistically significant. Specifically, the frequency intervals corresponded to a nitric oxide dependent endothelial activity. In addition, an excessive response induced by stretching in frequency intervals of neurogenic activity, when compared with the non-smoking control, was found on diabetic non-smokers. Conclusion: All subjects expressed the PSRH effect in cutaneous microcirculation after a 10-second stretch stimulus; however, this effect was observed at a significantly lower intensity in chronic smokers with diabetes. The spectral analysis of the skin blood flow signals provides a pathological index for the assessment of the endothelial dysfunction induced by cigarette smoking. Furthermore, the discrepancy of neurovascular function between that of diabetic non-smokers and normal subjects could also be distinguished via the variations of the spectrum related to neurogenic activity.